The autophagy initiator ULK1 sensitizes AMPK to allosteric drugs - Toby A. Dite (Nature Portfolio, 2017)
AMPK is involved in sensing of metabolic stress. The authors show that the autophagy initiator ULK1 phosphorylates β1-Ser108 on the regulatory β1-subunit, sensitizing AMPK to allosteric drugs, and activates signaling pathways that appear independent of Thr172 phosphorylation in the kinase activation loop.